Early reduction of skin potassium without sodium accumulation in the pathogenesis of salt sensitivity in primary aldosteronism - Mlejnek, Petr; Liška, František; Šilhavý, Jan; Večerková, Kateřina; Šimáková, Miroslava; Pravenec, Michal; Kurtz, Theodore W. (Frontiers in Pharmacology, 2025)
IntroductionPrimary aldosteronism is the most common form of secondary hypertension and blood pressure salt sensitivity. In the setting of hyperaldosteronism and a high-salt diet, disturbances in tissue sodium and potassium levels may contribute to salt sensitivity. This study aimed to determine whether aldosterone-dependent changes in tissue and plasma sodium and potassium concentrations occur before or after the development of salt sensitivity and hypertension in a rat model of primary aldosteronism. Previous studies in this model show that aldosterone-dependent salt sensitivity develops after 7–10 days on a high-salt diet. A secondary objective was to investigate differences in skin gene expression between aldosterone-treated rats and vehicle-treated controls.MethodsUnilaterally nephrectomized male Sprague-Dawley rats received continuous infusions of aldosterone or vehicle while being fed a high-salt diet. Electrolyte concentrations in plasma, carcass, and skin were measured after 2 and 14 days of high-salt feeding. Tissue sodium and potassium concentrations were determined by atomic absorption spectroscopy and expressed as mmol/g tissue dry weight, while plasma ions (mmol/L) were measured using ion-selective electrodes. RNA sequencing (RNAseq) was used to identify differentially expressed genes in the skin, and gene set enrichment analysis (GSEA) was performed to explore biological processes associated with aldosterone treatment.ResultsAfter 2 days on the high-salt diet, aldosterone-treated rats showed significantly lower skin and plasma potassium concentrations compared to vehicle-treated controls, while sodium concentrations in the carcass, skin, and plasma did not differ significantly. At 14 days, aldosterone-treated rats continued to exhibit lower plasma potassium levels, although skin potassium differences were no longer significant. Carcass sodium concentrations were significantly higher in aldosterone-treated rats at 14 days. GSEA revealed that, at 2 days, aldosterone treatment affected biological processes related to electrolyte homeostasis and hyperosmotic responses. At 14 days, biological processes related to muscle function and calcium ion transport were significantly altered.ConclusionAldosterone-treated rats on a high-salt diet for 2 days had lower skin and plasma potassium levels compared to salt-loaded controls, suggesting early potassium depletion precedes significant sodium accumulation and blood pressure increases. These findings raise the possibility that early potassium depletion contributes to the development of aldosterone-induced salt sensitivity. Further studies with detailed time-course analysis will be of interest to elucidate the role of early potassium depletion in increasing vascular resistance and triggering aldosterone-dependent salt sensitivity and hypertension.